Kebenaran dalam Media Digital - Editha Soebagio (Litbang STFT Widya Sasana Malang, 2020)
Abstraction : In just a decade, the truth that actually becomes a pillar in a life together turned out to be a lot of coloured falsehood and lies. The practice of manipulating the truth is rife because humans are in the post-truth era, an era where people are busy hiding the truth without making them feel dishonest. This situation is supported by the emergence of digital media which produces a lot of lies without going through the verification process. The claim of truth has been displaced by ‘believability’ and the institutionalization of lies is deliberately carried out to manipulate the truth. As a result the real news is a lie accepted as truth. And conversely the news that actually needs to be accepted as truth is considered a lie. This certainly brings harm to the people who should have the right to receive true news. In this situation, media literacy needs to be done so that people are responsible for promoting and spreading the right news based on the virtue of honesty. It requires hardwork and commitment, not just embrace the right for everyone to speak, but also to hear and listen, to discern which is the truth as best we can, not just for our present, but it will be very valuable for our future. Abstraksi : Dalam periode yang singkat, kebenaran yang sejatinya menjadi pilar dalam kehidupan bersama ternyata banyak diwarnai kepalsuan dan kebohongan. Praktek manipulasi kebenaran marak dilakukan dalam era post-truth, sebuah masa di mana orang ramai menyembunyikan kebenaran tanpa membuatnya merasa tidak jujur. Situasi ini didukung oleh munculnya media digital yang banyak memproduksi berita bohong tanpa melalui proses verifikasi. Kebenaran digantikan dengan kesesuaian dengan opini pribadi dan instusionalisasi kebohongan dengan sengaja dilakukan untuk memanipulasi kebenaran. Akibatnya berita yang sebenarnya merupakan kebohongan diterima sebagai kebenaran, dan sebaliknya berita yang sebenarnya perlu diterima sebagai kebenaran dianggap sebagai kebohongan. Hal ini tentu membawa kerugian bagi masyarakat yang seharusnya memiliki hak untuk menerima berita yang benar. Dalam situasi ini, literasi media perlu dilakukan agar orang bertanggung jawab mempromosikan dan menyebarkan berita yang benar berlandaskan keutamaan kejujuran. Hal ini membutuhkan kerja keras dan komitmen, bukan hanya mengupayakan agar setiap orang dapat menyampaikan pendapatnya, tetapi juga untuk mendengarkan dan memahami, serta berusaha sebaik mungkin untuk mengupayakan kebenaran, bukan hanya untuk saat ini saja, tetapi akan sangat berharga untuk masa depan kita.